Assessing the awareness and perception of hoteliers towards shariah compliant hotel operations / Noor Azimin Zaino ... [et al.] - Zaino, Noor Azimin; Ahmad, Rozila; Ideris, Muhamad Shah Kamal; Nor Azam, Nor Rabiatul Adawiyah (Universiti Teknologi MARA Cawangan Sarawak, 2019)
Halal management has received a wide interest globally. One aspect under halal management is pertaining to halal hospitality, whereby the concept of shariah compliant hotels is considered as an innovative concept and has gained a lot of attention as of late. Shariah compliant concept has received special interest in various operations as the general public are increasingly more aware of the niche market that Islamic tourism has brought forward. However, the concept of Shariah compliance is seen as not well understood in the Malaysian context alas the implementation is still mediocre. This paper seeks to examine the awareness and perception of hoteliers towards Shariah concepts. Specifically, the purpose of this paper is to investigate the awareness and perception of hoteliers towards this concept from the perception of small and medium hotel operators. Qualitative approach was applied by carrying out face-to-face interviews with 11 hoteliers in the northern region of Malaysia. It was found that awareness on the definition of shariah compliance is a critical factor in implementing this concept, hence instilling awareness regarding the shariah compliant concept is crucial so that misconceptions are minimized. The significance of this study is to bring about awareness of Shariah hotel operations to the parties involved in the management of the hotel, tourists, hotel guests, owners, and other hospitality service companies. Data obtained from this study is forecasted to aid in awareness to the hotel management and stakeholders on the implementation of shariah practices. Hence, it contributes to the under-researched area of halal management for halal tourism sustainability in the long run.